Verizon vs AT&T. - Berenstain, Adam.; Vargus, Nick.
Which carrier deserves your iPhone? And should you wait for the iPhone 5 before considering a switch? We explain everything you need to know about both carriers their iPhones, and all their options.
Keywords: AT&T.; iPhone (Smartphone); Verizon; iPhone 4.